Vergifnis in die gebed van Daniël (Dan. 9:4-19) - D. F. O'Kennedy (Acta Theologica, 2003)
Daniel 9:4-19 is one of the important penitential prayers in the Old Testament. This prayer has been investigated from different perspectives, but the theological dimension of forgiveness is often neglected. In this article the understanding of divine forgiveness is studied and the following important elements are emphasised: (1) Forgiveness cannot be limited to one specific historical context; (2) The motivation for forgiveness does not lie in the people’s obedience, but in God’s grace and mercy; (3) The structure and content of the prayer implies that confession of guilt is an important element in the process of forgiveness. Everyone is guilty — the guilt is not placed on a certain person or king (cf. v. 7); (4) Forgiveness is meant for the “international” Israel and not limited to a specific geographical area.